The Influence of Islamic Banking Financial Technology on Financial Inclusion: A Case Study - Anika, Regi; Harahap, Muhammad Ikhsan; Syafina, Lailan (Journal La Sociale, 2023)
This research aims to analyse the role of Fintech in increasing financial inclusion for customers of Bank Sumut Syariah KCP Lubuk Pakam. Fintech as a combination of finance and technology, offers faster, more efficient and inclusive solutions for accessing financial services. This research uses a quantitative approach to analyse data obtained from a survey of customers of Bank Sumut Syariah KCP Lubuk Pakam. The quantitative method was chosen as a way to find out the result of this research because it allows researches to collect data that can be measured statistically, so that they can identify patterns and trends in the relationship between variables, namely the use of Financial Technology (Fintech) in sharia banking (X) with the development of financial inclusion (You). The research result shows that Fintech plays a significant role in facilitating access to financial services. Fintech also contributes to increasing financial literacy, transaction efficiency and customer trust through advanced security features such as data encryption and multi-factor authentication. This research provides recommendationsfor improving digital infrastructure, financial education, and developing innovative sharia products and services.